Niveles contrastantes de fructosa y urea agregados a una dieta basada en raigrás anual: efectos sobre síntesis de proteína microbiana, digestibilidad de nutrientes y parámetros de fermentación en fermentadores de flujo continuo (Semiárida, 2019)
The objective of this experiment was to evaluate the effects of the addition of crystalline fructose and urea to an annual ryegrassbased diet on microbial protein synthesis, fermentation profile and nutrient apparent digestibility, using continuous culture fermenters. Six fermenters were used in a 3 x 2 factorial arrangement with three levels of water soluble carbohydrates (WSC) obtained by crystalline fructose addition (21, 24 and 27 g.100 g DM1; LWSC, MWSC and HWSC, respectively) and two levels of CP obtained by urea addition (14.6 and 18.6 g.100 g DM1, LCP and HCP, respectively). Four 10d periods were ran sequentially (7d for adaptation, 3d for sampling). Microbial protein synthesis was assessed by purine to N ratio. There was a positive interaction between WSC and CP level on microbial protein synthesis (P
Keywords: annual ryegrass; continuous culture; crude protein; microbial protein synthesis; water soluble carbohydrate